Immune Cell-Epithelial/Mesenchymal Interaction Contributing to Allergic Airway Inflammation Associated Pathology - Hirahara, Kiyoshi; Shinoda, Kenta; Morimoto, Yuki; Kiuchi, Masahiro; Aoki, Ami; Kumagai, Jin; Kokubo, Kota; Nakayama, Toshinori (Frontiers in Immunology, 2019)
The primary function of the lung is efficient gas exchange between alveolar air and alveolar capillary blood. At the same time, the lung protects the host from continuous invasion of harmful viruses and bacteria by developing unique epithelial barrier systems. Thus, the lung has a complex architecture comprising a mixture of various types of cells including epithelial cells, mesenchymal cells and immune cells. Recent studies have revealed that Interleukin (IL-)33, a member of the IL-1 family of cytokines, is a key environmental cytokine that is derived from epithelial cells and induces type 2 inflammation in the barrier organs, including the lung. IL-33 induces allergic diseases, such as asthma, through the activation of various immune cells that express an IL-33 receptor, ST2, including ST2+ memory (CD62LlowCD44hi) CD4+ T cells. ST2+ memory CD4+ T cells have the capacity to produce high levels of IL-5 and Amphiregulin and are involved in the pathology of asthma. ST2+ memory CD4+ T cells are maintained by IL-7- and IL-33-produced lymphatic endothelial cells within inducible bronchus-associated lymphoid tissue (iBALT) around the bronchioles during chronic lung inflammation. In this review, we will discuss the impact of these immune cells-epithelial/mesenchymal interaction on shaping the pathology of chronic allergic inflammation. A better understanding of pathogenic roles of the cellular and molecular interaction between immune cells and non-immune cells is crucial for the development of new therapeutic strategies for intractable allergic diseases.